Investigating Lignin Key Features in Maize Lignocelluloses Using Infrared Spectroscopy. Issue 12 (December 2014) - Chazal, Richard; Robert, Paul; Durand, Sylvie; Devaux, Marie-Françoise; Saulnier, Luc; Lapierre, Catherine; Guillon, Fabienne
Lignins and their cross-linking to hemicelluloses detrimentally affect the cellulose-to-ethanol conversion of grass lignocelluloses. Screening appropriate grass cell walls and their compositional changes during the various steps of the process calls for a high-throughput analytical technique. Such a performance can be fulfilled by Fourier transform mid-infrared (FT-MIR) spectroscopy. In the present paper, a set of maize cell walls from mature stems were selected, including brown midrib samples. Lignin fractions were isolated by mild acidolysis to obtain a set of purified maize lignin standards. The lignin content and the percentage of lignin-derived p -hydroxyphenyl (H), guaiacyl (G), and syringyl (S) thioacidolysis monomers were determined. In addition, the composition of cell wall polysaccharides, as well as the amount of ester-linked p -coumaric (CA) and ferulic (FA) acids, was measured by wet chemistry. Partial least square (PLS) analyses were applied to infrared and chemical data of cell walls. The resulting models showed a good predictive ability with regard to the lignin content, to the frequency of S (or G) thioacidolysis monomers, and to the level of ester-linked CA of maize cell walls. The loading plots and regression coefficients revealed relevant infrared absorption bands.